Seaweed Diversity at Batu Lawang Beach, Sengkol Village, Pujut District, Central Lombok Regency - Cokrowati, Nunik; Yatin, Nur; Rahmadani, Thoy Batun Citra; Rusman, Rusman; Ahmad, Ahmad; Sukriadi, Sukriadi; Pebriata, M. Nurdian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Seaweed is a marine and fisheries resource that is currently widely utilized by aquaculture communities and coastal fishermen, because in addition to being easy to maintain, it also provides economic benefits. Batu Lawang beach has the potential for natural grass resources that can be developed. This can be seen from the condition of the water quality in the waters. Some types of seaweed that are cultivated are Kappaphycus alvarezii and Eucheuma spinosum. Batu Lawang beach is an area that has a variety of macroalgae, as well as a fairly large coral reef area. Therefore, this research was carried out to find out the types of macroalgae in the Batu Lawang Beach area. The research was conducted in May-June 2024. This research location is located at Batu Lawang Beach, Gerupuk, Sengkol Village, Pujut District, Central Lombok Regency. This research used purposive sampling method. The results of this study, seaweed that grow naturally are Acanthophora spicifera, Gracilaria verrucosa, Sargassum cristaefolium, Gracilaria coronopifolia, Valoniopsis pachynema, Ulva, K. alvarezii, Halimeda opuntia, Eucheuma spinosum, Dictyopteris dichotoma, Laurencia papillosa, Codium fragile, Padina sp., Turbinaria decurrens, Halimeda tuna, Gracilaria sp. The conclusion is the is 16 types of seaweed that grow wild, with each type containing different antioxidants and chlorophyll-a.